PERBANDINGAN ANTARA MODEL PEMBELAJARAN BERBASIS PROYEK DAN MODEL PEMBELAJARAN BERBASIS MASALAH DALAM MENINGKATKAN KEMAMPUAN KRITIS SISWA - NOURMA, NOURMA YUNITA (Universitas Muhammadiyah Gresik, 2024)
This study aims to find out how well the project-based learning model and problem-based learning model improve students' critical thinking skills. The results showed that students who participated in project-based learning showed significant improvements in their collaboration and critical thinking skills. With the development of the times and the acceleration of digitalization caused by the pandemic, PjBL can be combined with Blended Learning.Thus, the Project Based Blended Learning (PjB2L) model has been created. Many current studies show that PjB2L can improve the quality of learning. This study aims to theoretically explain the results of research on the application of the PjB2L model at various levels of education, from elementary school to tertiary. The method of this research is qualitative, and a literature study approach involving various literatures is used in this study According to this study, the implementation of PjB2L is considered successful and has a positive impact on learning outcomes